2015
DOI: 10.1002/ams2.141
|View full text |Cite
|
Sign up to set email alerts
|

Use and effectiveness of prothrombin complex concentrate in an emergency department: a review of 15 cases

Abstract: Aim: Hemostatic management of patients on oral anticoagulant therapy with critical bleeding continues to be a major challenge. The present study aimed to validate the efficacy, safety, and optimal dosage of prothrombin complex concentrate for rapidly normalizing elevated international normalized ratio (INR) values and achieving control of hemorrhage at an emergency department in Japan. Methods:We retrospectively collected data from all patients who were treated with PCC at our emergency department between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Инфузию КПК осуществляли при помощи препарата протромплекс 600 («Baxter», Австрия), который содержит в пропорциональном соотношении прокоагулянты: 4 витамин K-зависимых фактора свертывания (II, VII, IX, X) и естественные антикоагулянты: протеин С, антитромбин III и небольшую дозу гепарина, который предупреждает активацию факторов свертывания в процессе приготовления раствора перед введением пациенту. Дозу препарата определяли по исходному МНО, согласно данным японских исследователей [16][17][18] за счет высокой концентрации основных факторов свертывания: в 1 мл КПК в 25-30 раз выше, чем в 1 мл СЗП. После введения КПК кровотечение было остановлено у всех больных и повторного введения препарата не потребовалось.…”
Section: материал и методыunclassified
“…Инфузию КПК осуществляли при помощи препарата протромплекс 600 («Baxter», Австрия), который содержит в пропорциональном соотношении прокоагулянты: 4 витамин K-зависимых фактора свертывания (II, VII, IX, X) и естественные антикоагулянты: протеин С, антитромбин III и небольшую дозу гепарина, который предупреждает активацию факторов свертывания в процессе приготовления раствора перед введением пациенту. Дозу препарата определяли по исходному МНО, согласно данным японских исследователей [16][17][18] за счет высокой концентрации основных факторов свертывания: в 1 мл КПК в 25-30 раз выше, чем в 1 мл СЗП. После введения КПК кровотечение было остановлено у всех больных и повторного введения препарата не потребовалось.…”
Section: материал и методыunclassified
“…However, the most effective dosing regimen for PCC in cardiac injury is still uncertain. According to our recent report, 4 PCC provide rapid (within 30 min) reversal of warfarin-related coagulopathy, but fixed dose of 500 IU may be insufficient for normalization of prolonged INR value. Moreover, the effectiveness of PCC for NOAC has not been confirmed.…”
Section: Usefulness Of Prothrombin Complex Concentrate For Cardiac Inmentioning
confidence: 99%
“…In addition, its use is limited to patients with INR over 2. However, rapid normalization of INR during hemostatic management is necessary even in patients with critical bleeding who do not meet the treatment criterion 14,15 . Although PCC has emerged as the preferred option in emergency settings, the optimal dosing strategy, especially in Japanese patients, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We reported 15 cases of PCC treatment in the emergency department (ED) in 2015 and found that a fixed PCC dose of 500 IU is insufficient in some patients with INR elevation 14 . Conversely, this dose was effective in patients with INR less than 2.5 14 . On the basis of these findings, in October 2014, our institution implemented a two‐level fixed‐dose initiation strategy for PCC featuring an initial dose of 500 or 1,000 IU according to the initial INR (Fig.…”
Section: Introductionmentioning
confidence: 99%